Identification of novel genes associated with herbicide tolerance in Lentil (Lens culinaris ssp. culinaris Medik.) - Balech, Rind; Maalouf, Fouad; Kaur, Sukhjiwan; Jighly, Abdulqader; Joukhadar, Reem; Alsamman, Alsamman M.; Hamwieh, Aladdin; Abou-Khater, Lynn; Rubiales, Diego; Agrawal, Shiv Kumar (Nature Publishing Group: Open Access Journals - Option C, 2024)
Weeds pose a major constraint in lentil cultivation, leading to decrease farmers’ revenues by reducing the yield and increasing the management costs. The development of herbicide tolerant cultivars is essential to increase lentil yield. Even though herbicide tolerant lines have been identified in lentils, breeding efforts are still limited and lack proper validation. Marker assisted selection (MAS) can increase selection accuracy at early generations. Total 292 lentil accessions were evaluated under different dosages of two herbicides, metribuzin and imazethapyr, during two seasons at Marchouch, Morocco and Terbol, Lebanon. Highly significant differences among accessions were observed for days to flowering (DF) and maturity (DM), plant height (PH), biological yield (BY), seed yield (SY), number of pods per plant (NP), as well as the reduction indices (RI) for PH, BY, SY and NP. A total of 10,271 SNPs markers uniformly distributed along the lentil genome were assayed using Multispecies Pulse SNP chip developed at Agriculture Victoria, Melbourne. Meta-GWAS analysis was used to detect marker-trait associations, which detected 125 SNPs markers associated with different traits and clustered in 85 unique quantitative trait loci. These findings provide valuable insights for initiating MAS programs aiming to enhance herbicide tolerance in lentil crop.